Early Thyroid Volume Reduction in Subacute Thyroiditis Can be a Potential Indicator for Hypothyroidism - Park, Ji Yong; Choi, Wonsuk; Hong, A Ram; Yoon, Jee Hee; Kim, Hee Kyung; Kang, Ho-Cheol (Frontiers in Endocrinology, 2022)
Background: Thyroid volume has been reported to decrease significantly after episodes of subacute thyroiditis (SAT); however, the relationship between thyroid volume and hypothyroidism remains unclear. This study assessed the association between thyroid volume changes and the hypothyroid phase in patients with SAT, a condition that can progress to persistent hypothyroidism. Methods: This retrospective study evaluated 37 patients diagnosed with SAT at the Department of Endocrinology and Metabolism of Chonnam National University Hwasun Hospital (CNUHH) between 2016 and 2021. Since we could not determine the clinical characteristics of patients with SAT before their episodes, 120 healthy individuals who underwent thyroid ultrasonography during regular check-ups from 2019 to 2021 at CNUHH were selected for comparison. Subgroup analyses were performed on patients with SAT with and without the hypothyroid phase during their clinical course. Results: Thyroid volume was significantly greater in SAT patients at the first visit than in controls (p<0.05), and it decreased constantly throughout the follow-up period. Subgroup analysis showed that the initial thyroid volumes were similar in patients with SAT with and without the hypothyroid phase. However, SAT patients with the hypothyroid phase had significantly smaller thyroid volumes at the 1 month (p=0.025) and 3 month (p=0.006) follow-up visits. The reduction rate of the thyroid volume was significantly different within the first month (p=0.009). Conclusion: A greater reduction in thyroid volume in SAT patients within 1 month of episode had a higher chance of developing a subsequent hypothyroid phase, which can lead to persistent hypothyroidism. Serial thyroid ultrasonography in patients with SAT, especially within the first month, may help in predicting the disease course of SAT.